Aboriginal and Torres Strait Islander Australians and the Superannuation System - Dockery, Michael (Bankwest Curtin Economics Centre, 2020)
This report assesses the appropriateness of the Superannuation system for Indigenous Australians, based on a combination of quantitative modelling and qualitative research. It highlights the importance of creating a more culturally-aligned superannuation system that provides greater support to Indigenous Australians who may be experiencing significant disadvantage or hardship and offers some important insights that improve our understanding of the financial security – or otherwise – that the current retirement system offers to Indigenous Australians and their families.